Policy Advisers in Renewable Energies Policies in Portugal: Dynamics, Influence and Structural Constraints - Conceição, M.; Asensio, M.; Mazeda Gil, P. (International Public Policy Association (IPPA), 2025)
This paper examines the policy advice of renewable energies policies in Portugal through the lens of the Policy Advisory Systems framework. The study analyzes how different actors—including political advisers, public entities, academics, industry representatives, and civil society organizations— contribute to policy design and decision-making in the field. In addition to mapping this policy advice network, highlighting its main actors and their level of influence, the paper also explores four key hypotheses about this advisory network’s dynamics: the decline of the state’s policy advisory capacity in the energy sector; the politicization and externalization of policy advice in the field; and its “capture” by private corporate interests. The findings suggest that Portugal's renewable energies policies, in recent years, result from an increasingly centralized advisory process within decision-makers' cabinets and energy producers representatives, with public entities, academics and other civil society organizations having a secondary and marginal role in advising policymaking in the sector. In terms of policy impact, the predominance of this type of policy advisers may reflect an approach that prioritizes renewable energy as a driver of economic development and geopolitical leadership, while sidelining issues of energy justice, such as the impacts of megaprojects on communities and territories, as well as the need to mitigate the harms caused by the renewable energy industry. By shedding light on the structural constraints and power asymmetries within Portugal’s energy advisory landscape, this study advances the literature on policy advice in underexplored national contexts and deepens our understanding of how advisory dynamics shape energy transition outcomes.